Age‐dependent mesial temporal lobe lateralization in language fMRI. (23rd December 2015) - Sepeta, Leigh N.; Berl, Madison M.; Wilke, Marko; You, Xiaozhen; Mehta, Meera; Xu, Benjamin; Inati, Sara; Dustin, Irene; Khan, Omar; Austermuehle, Alison; Theodore, William H.; Gaillard, William D.
Summary: Objective: Functional magnetic resonance imaging (fMRI) activation of the mesial temporal lobe (MTL) may be important for epilepsy surgical planning. We examined MTL activation and lateralization during language fMRI in children and adults with focal epilepsy. Methods: One hundred forty‐two controls and patients with left hemisphere focal epilepsy (pediatric: epilepsy, n = 17, mean age = 9.9 ± 2.0; controls, n = 48; mean age = 9.1 ± 2.6; adult: epilepsy, n = 20, mean age = 26.7 ± 5.8; controls, n = 57, mean age = 26.2 ± 7.5) underwent 3T fMRI using a language task (auditory description decision task). Image processing and analyses were conducted using Statistical Parametric Mapping (SPM8); regions of interest (ROIs) included MTL, Broca's area, and Wernicke's area. We assessed group and individual MTL activation, and examined degree of lateralization. Results: Patients and controls (pediatric and adult) demonstrated group and individual MTL activation during language fMRI. MTL activation was left lateralized for adults, but less so in children (p's < 0.005). Patients did not differ from controls in either age group. Stronger left‐lateralized MTL activation was related to older age (p = 0.02). Language lateralization (Broca's and Wernicke's) predicted 19% of the variance in MTL lateralization for adults (p = 0.001), but for not children. Significance: Language fMRI may be used to elicit group and individual MTL activation. The developmental difference in MTL lateralization and its association with language lateralization suggests a developmental shift in lateralization of MTL function, with increased left lateralization across the age span. This shift may help explain why children have better memory outcomes following resection compared to adults.